Predicting the impact of land-use changes on soil erosion rates in the three small sub-catchments of Larona Catchment. Issue 2 (July 2021) - Achmad, M; Samsuar,; Lanuru, M; Mubarak, H
Abstract: This study aims to predict the amount of soil erosion in the three sub-catchments of Larona Catchment, which are Larona, Balambano, and Karebbe sub-catchments. The USLE method is used to predict soil erosion rates in 2009 and 2015 by using rainfall data of 13 rainfall stations, soil maps, DEM data for generating LS factors, Landsat 8 Imageries, and land use maps create CP factors. Four thematic maps (R, K, LS, and CP) were overlaid and clustered using ArcGIS 10.4. The results show that soil erosion rates in the period of 6 years have changed in the three sub-catchments. The erosion rate in Larona and Karebbe sub-catchment slightly increased from 43, 092 tons to 50, 982 and 155, 005 tons to 224, 757 tons, respectively, from 2009 to 2015. In the Balambano sub-catchment, the value of erosion rate increased dramatically during the period. Total erosion this sub-catchment in 2015 became 5 to 7 times of the total erosion in 2009. The change of land use caused the increased sediment yields in the three cascade-reservoirs in Larona Catchment and land cover, mostly the result of increasing agricultural activities and not due to mining development.